Charge state of the activator in Ti:sapphire crystals grown by HDC method - Sidelnikova, N.S.; Nizhankovskyi, S.V.; Baranov, V.V. (Functional Materials, 2015)
The results of the study of the charge state of the activator ([Ti³⁺], [Ti⁴⁺]) in Ti:sapphire crystals grown by the method of horizontal directed crystallization, are presented. It is shown that, depending on the pressure, the growth medium composition and the conditions of annealing of the crystals with 0.03-0.1 wt. % titanium content, the ratio of the content of the activator in the charge state [Ti⁴⁺] to the one in [Ti³⁺] state is ~0.23-3.3 %. There are obtained approximate analytical dependences of [Ti⁴⁺] and [Ti⁴⁺]/[Ti³⁺] on the partial pressure of molecular oxygen and the total concentration of the activator which provide a reliable description of the experimental data. It is established that though with the growth of the total concentration of the activator the value of the ratio [Ti⁴⁺]/[Ti³⁺] decreases to ~ [Titot]-1/4, the concentration of the activator in the charge state Ti4+ rises to ~ [Titot]3/4. This may be accompanied with the increase of the quantity of the absorption centers at 800 nm (Ti³⁺-Ti⁴⁺-centers) and, consequently with the figure of merit (FOM).